Rare SNP rs12731181 in the miR-590-3p Target Site of the Prostaglandin F2α Receptor Gene Confers Risk for Essential Hypertension in the Han Chinese Population. Issue 7 (July 2015) - Xiao, Bing; Gu, Shui-Ming; Li, Mulin Jun; Li, Jun; Tao, Bo; Wang, Yuanyang; Wang, Yan; Zuo, Shengkai; Shen, Yujun; Yu, Yu; Chen, Di; Chen, Guilin; et al.
Abstract : Objective—: To investigate whether rs12731181 (A→G) interrupted miR-590-3p–mediated suppression of the prostaglandin F2α receptor (FP) and whether it is associated with essential hypertension in the Chinese population. Approach and Results—: We found that miR-590-3p regulates human FP gene expression by binding to its 3′-untranslated region. rs12731181 (A→G) altered the binding affinity between miR-590-3p and its FP 3′-untranslated region target, thus reducing the suppression of FP expression, which, in turn, enhanced FP receptor–mediated contractility of vascular smooth muscle cells. Overexpression of FP augmented vascular tone and elevated blood pressure in mice. An association study was performed to analyze the relationship between the FP gene and essential hypertension in the Han Chinese population. The results indicated that the rs12731181 G allele was associated with susceptibility to essential hypertension. Carriers of the AG genotype exhibited significantly higher blood pressure than those of the AA genotype. FP gene expression was significantly higher in human peripheral leukocytes from individuals with the AG genotype than that in leukocytes from individuals with the AA genotype. Conclusions—: rs12731181 in the seed region of the miR-590-3p target site is associated with increased risk of essential hypertension and represents a new paradigm for FP involvement in blood pressure regulation. Abstract : Supplemental Digital Content is available in the text.